STM investigations on bridged macrocyclic metal complexes - Aldinger, R.; Hanack, Michael; Herrmann, K.-H.; Hirsch, Andreas; Kasper, K. (Synthetic Metals, 1993)
The non-crystallizable bridged phthalocyaninatoiron complexes, [(tBu)PcFe(dib)] (1) and [(tBu)PcFe(mepyNC)] (2), were spread onto highly oriented pyrolytic graphite and imaged using scanning tunnelling microscopy in air. Dominating parallel arrangements of the oligomeric molecules in bundles of two to five stacks have been found. The individual building blocks, namely, the macrocycles (tBu)PcFe and the bridging ligands 1,4-diisocyanobenzene (dib) and 4-isocyano-3,5-dimethylpyridine (mepyNC), however, could not be resolved. Possible reasons include the non-pronounced molecular structure, a non-perfect solvent removal and the strong electric force of the tip to the weakly bonded molecule. The width (about 15 Å) and the length (80 to 450 Å) of the single oligomer stacks agree well with the structure model and, with respect to the chain lengths, the results of non-spatially resolving measuring methods. © 1993.